Antibacterial of Clostridium botulinum From Eagle Flower (Clitoria ternatea L.) Kombucha Body Wash as a Pharmaceutical Biotechnology Product - Hari Hariadi; Titin Sulastri; Firman Rezaldi; Susanti Erikania; Rina Nurmaulawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Liquid bath soap made from telang flower kombucha fermented solution has potential as a pharmaceutical biotechnology product in inhibiting the growth of Clostridium botulinum bacteria. The aim of this study was to formulate and prepare a liquid bath soap with an active ingredient based on fermented eggplant kombucha solution in inhibiting the growth of Clostridium botulinum bacteria. The research design was carried out experimentally by making four liquid body wash preparations consisting of body wash base ingredients without active substances as negative controls. The basic ingredients for bath soap with the active ingredient are fermented butterfly pea flower kombucha solution with a concentration of 20%; 30%; and 40%. Disc diffusion is a test method used to inhibit the growth of test bacteria from each soap preparation. One way ANOVA and post hoc analysis are methods used to statistically analyze all liquid body wash preparations to see their effect on the growth of the test bacteria. The results of the study were proven and it can be concluded that based on one way ANOVA with a p value <0.05, 40% concentration of telaga kombucha bath soap is the best treatment for inhibiting the growth of test bacteria with an average diameter of the resulting inhibition zone of 18.50 mm and entering the strong category. The concentration of 40% was significantly different in inhibiting the growth of the test bacteria compared to the concentrations of 20% and 30% but not significantly different from the bath soap on the market as a positive control.